Castleman Disease: A Multicenter Case Series from Turkey - Gunduz, Eren; Kirkizlar, Hakki Onur; Umit, Elif Gulsum; Gulsaran, Sedanur Karaman; Ozkocaman, Vildan; Ozkalemkas, Fahir; Ozturk, Sule Mine Bakanay (Galenos Publ House, 2022)
Objective: Castleman disease (CD) is a rare disease also known as angiofollicular lymph node hyperplasia. The two main histological subtypes are the hyaline vascular and plasma cell variants. It is further classified as unicentric CD (UCD) or multicentric CD (MCD) according to the anatomical distribution of the disease and the number of lymph nodes involved. The aim of this multicenter study was to evaluate all cases of CD identified to date in Turkey to set up a national registry to improve the early recognition, treatment, and follow-up of CD. Materials and Methods: Both adult (n=130) and pediatric (n=10) patients with lymph node or involved field biopsy results reported as CD were included in the study. Patients' demographic information, clinical and laboratory characteristics, imaging study results, treatment strategies, and clinical outcomes were evaluated retrospectively. Results: A total of 140 patients (69 male and 71 female) with a diagnosis of UCD (n=73) or MCD (n=67) were included. The mean age was 39 years in the UCD group and 47 years in the MCD group. Female patients were more common in the UCD group. The most common histological subtype was hyaline vascular for both UCD and MCD patients. Asymptomatic patients were more common in the UCD group. Anemia, elevations of acute phase reactants, and hypoalbuminemia were more common in the MCD group. The most commonly used treatment strategies for UCD were surgical excision, rituximab, and radiotherapy, respectively. All UCD patients were alive at a median of 19.5 months of follow-up. The most commonly used treatment strategies for MCD were methyl prednisolone, R-CHOP, R-CVP, and rituximab. Thirteen MCD patients had died at a median of 34 months of follow-up. Conclusion: This study is important in presenting the patient characteristics and treatment strategies for CD from Turkey, with the potential of increasing awareness about CD. Treatment data may help in making decisions, particularly in countries that do not have access to siltuximab. However, larger prospective studies are needed to make definitive conclusions.
Castleman Hastalığı: Türkiye’den Çok Merkezli Bir Olgu Serisi
Keywords: Castleman disease; Unicentric; Multicentric; Treatment